Architecture and Sustainability Pathways for Rural Development in Indonesia - Saskia, Cut Sannas; Kridarso, Etty Retnowati; Fatmasari, Ulfa; Winandari, Maria Immaculata Ririk (RUSTIC, 2026)
Rural landscapes in Indonesia reflect the coexistence of strong agrarian traditions and the pressing need for sustainable development, requiring approaches that integrate ecological, spatial, and socio-economic systems. Ciambar District in Sukabumi Regency, West Java, serves as a representative case study, characterized by agricultural activities such as rice, cassava, and durian cultivation, extensive forest areas, and ecotourism potential, including Curug Luhur Waterfall. Despite these assets, the district faces persistent challenges, including inadequate infrastructure, unequal access to clean water, and heavy reliance on small-scale agriculture. From the perspective of architectural sustainability, Ciambar must be re-envisioned as an integrated landscape of productive, ecological, and social spaces. Approaches such as productive landscapes, ecological infrastructure, and low-impact ecotourism demonstrate how spatial and architectural interventions can simultaneously support livelihoods, conserve ecosystems, and enhance local resilience. This study aims to identify, analyze, and map the potentials of Ciambar District based on natural resources, human capital, and local governance capacity. The findings are expected to provide a comprehensive assessment of existing strengths and opportunities, along with strategic recommendations for sustainable environmental development that supports the local economy while aligning with broader sustainability frameworks.